Juridical analysis of policy concerning oil palm estate management in Indonesia - Prischa Listiningrum; Rizqi Bachtiar; Dararida Fandra Mahira; Rumi Suwardiyati (Faculty of Law, University of Muhammadiyah Malang, 2021)
The development of the palm oil industry (CPO) in Indonesia is often confronted by challenges coming from the international community, one of which is the rejection of Indonesian CPO exports declared by the European Union on the grounds of deforestation and land clearing, specifically forest burning, that are aimed to convert the forest areas to oil palm estates. In an attempt to clean such a bad name in palm oil industries in the world and to avert the label ‘unsustainable’ given by European Union, President Joko Widodo issued Presidential Instruction Number 8/2018. However, the implementation of the Presidential Instruction is not without hurdles like the absence of specific guidelines to help to implement the policy at the regional level and the lack of opportunities to involve civilians to guard this policy. Juridical analysis of the policy aimed to improve palm oil management and to hamper deforestation is, thus, required. With the normative-juridical method, this research is aimed to recommend the government to grow the potential of CPO-based biofuel in Indonesia and the application of a one-map policy over the potential of oil palm estates to allow the implementation of transparency principle in the structure of good governance. All these recommendations are mainly aimed to give more opportunities to the members of the public to have meaningful participation as well as sustainable and enviro-friendly in improving the management of palm oil cultivation.